Epoxides as Dual-Functionalized Alkylating Reagents in Catellani Reactions for the Assembly of Heterocycles - Wu, Chenggui; Cheng, Hong-Gang; Zhou, Qianghui (Synlett, 2020)
Reported is a cooperative catalytic system consisting of a complex of Pd with dicyclohexyl(2′,4′,6′-triisopropylbiphenyl-2-yl)phosphine (XPhos) and the potassium salt of 5-norbornene-2-carboxylic acid that permits the use of epoxides as dual-functionalized alkylating reagents in Catellani-type reactions for the assembly of heterocycles. Salient features of this research include readily available substrates, use of the potassium salt of 5-norbornene-2-carboxylic acid as a catalytic mediator as well as a base, and excellent regioselectivity for the cleavage of epoxides. This mild, chemoselective, scalable, atom- and step-economic protocol offers a straightforward approach for the assembly of isochroman and 2,3-dihydrobenzofuran scaffolds.
Keywords: Catellani reaction; cooperative catalysis; epoxides; isochromans; dihydrobenzofurans